1949
DOI: 10.1038/icb.1949.50
|View full text |Cite
|
Sign up to set email alerts
|

THE THERMAL DESTRUCTION OF VITAMIN B1

Abstract: The only attempt thus far to determine the effeet of temperature on the rate of destiHu-tiou of aneurin is that of Riee and Beuk (1945), wlio studied the rate of destruction of aneuriu in pork at temperatures from 121° 0. to 49° C. Tlicy show a doviaiinii ffom the Arrhcuins etiuation (whieh relates lop; /.• and 1/T) below 77" C. which could bo related to enzyme activity. It has been shown iti the earlier papers of this series that the effect of various faetors on the rate of destruction of aneurin can be motli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1955
1955
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…These results indicate that in the cleavage of thiamin by sulphite, in an aqueous solution at pH 5-0 and 250 and at the concentrations of the reactants tested, the overall reaction is unimolecular with respect to thiamin. Farrer (1945) andFarrer &Morrison (1949) also found that the destruction of thiamin in boiling solutions was a first-order reaction with respect to thiamin. The specific reaction-rate constant they reported, however, varied with pH and type of buffer.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that in the cleavage of thiamin by sulphite, in an aqueous solution at pH 5-0 and 250 and at the concentrations of the reactants tested, the overall reaction is unimolecular with respect to thiamin. Farrer (1945) andFarrer &Morrison (1949) also found that the destruction of thiamin in boiling solutions was a first-order reaction with respect to thiamin. The specific reaction-rate constant they reported, however, varied with pH and type of buffer.…”
Section: Resultsmentioning
confidence: 99%
“…There are conflicting reports on the effect of oxygen on thiamin degradation. Farrer and Morrison (1949) reported that oxygen can accelerate thermal destruction of thiamin in buffer solution at temperatures greater than 70°C. Williams and Spies (1938) and Mulley et al (1975) concluded that destruction of thiamin was not oxidative.…”
Section: Introductionmentioning
confidence: 99%
“…Thiamin degradation has been studied in the presence of several different contact surfaces and under diverse conditions. Thiamin solutions have been autoclaved in lacquer-lined cans Liska, 1971,1972) and in glass vials Arnold, 1972,1973;; sealed in glass tubes and immersed in hot water (Arnold et al, 1969;Higuchi, 1962,1963;Beadle et al, 1943;Mclntire and Frost, 1944); boiled and refluxed in glass systems (Booth, 1943;Farrer, 1945aFarrer, ,b, 1947aFarrer, ,b, 1948Farrer, ,1953Farrer, ,1955Farrer and Morrison, 1949); and injected directly into a steam-filled stainless steel chamber (Mulley et al, 1975a,b). The different kinetic parameters reported in these studies may be attributed partly to the catalytic effects of the contact materials on thiamin degradation.…”
Section: Literature Citedmentioning
confidence: 99%